2019
DOI: 10.1002/macp.201900051
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ester Free Type Poly(trimethylene carbonate) Derivatives with Pendant Fluoroaromatic Groups

Abstract: The facile method for the synthesis of ester free type poly(trimethylene carbonate) (PTMC) derivatives is previously reported. In this paper, a series of PTMC derivatives with fluoroaromatic groups in the side chain are synthesized to improve polymer properties. Thermal analysis reveals that all the PTMC derivatives have a decomposition temperature exceeding 300 °C. Furthermore, as the number of fluorine attached to the aromatic ring increases, the glass transition temperature decreases. In order to clarify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…36 The results were similar to those of Nobuoka et al where the introduction of aromatic derivatives into the side chain of PTMC yielded a T g of up to 1 1C. 37 The presence of an SU group in the side chain of PTMC further improved T g , suggesting the presence of self-association hydrogen bonding of the polymer chains. This is supported by the findings of Shieh et al who showed that incorporating acrylic acid units into poly(N-isopropylacrylamide) (PNIPAAm) tended to increase the T g due to strong hydrogen bonding between the amide groups present in the PNIPAAm.…”
Section: Thermal Stabilitysupporting
confidence: 79%
See 1 more Smart Citation
“…36 The results were similar to those of Nobuoka et al where the introduction of aromatic derivatives into the side chain of PTMC yielded a T g of up to 1 1C. 37 The presence of an SU group in the side chain of PTMC further improved T g , suggesting the presence of self-association hydrogen bonding of the polymer chains. This is supported by the findings of Shieh et al who showed that incorporating acrylic acid units into poly(N-isopropylacrylamide) (PNIPAAm) tended to increase the T g due to strong hydrogen bonding between the amide groups present in the PNIPAAm.…”
Section: Thermal Stabilitysupporting
confidence: 79%
“…36 The results were similar to those of Nobuoka et al where the introduction of aromatic derivatives into the side chain of PTMC yielded a T g of up to 1 °C. 37 The presence of an SU group in the side chain of PTMC further improved T g , suggesting the presence of self-association hydrogen bonding of the polymer chains.…”
Section: Resultsmentioning
confidence: 94%
“…[ 26 ] We also improved a synthetic pathway for ester free type TMC derivatives, [ 27 ] which brought wider variation of PTMC derivatives. [ 28 ] Although various materials have been successful with ester‐free PTMC, application as a stent coating material has yet to be achieved. We believe PTMC derivatives are useful for stent coating, because PTMC is more flexibile [ 29,30 ] compared with other biodegradable polyesters.…”
Section: Introductionmentioning
confidence: 99%